Contribution of Islamic Law in Tackling Money Laundering Crimes in Indonesia - Muhammad Ridha Haykal Amal (International Journal Reglement & Society (IJRS), 2021)
Money laundering is an attempt by a person to hide the origin of the proceeds of the crime he has committed. When viewed from the origin of the word, money laundering comes from two syllables, namely washing and money. Washing means cleaning something dirty or attempts to remove dirt stuck to something, and money is a tool that is used to exchange something and is generally accepted. In Jinayah's point of view, money / property is obtained from a way that is vanity / haram, for example, obtained from taking / seizing property that is not his property, narcotics, terrorism and so on. On that basis, in order to eliminate traces of his / her crime, a person then laundered the